A can of worms: Identification issues and morphological conservatism in a large sample of African Green and Bush Snakes (Colubridae: Philothamnus) from Minziro Forest, Tanzania. Issue 2 (10th December 2021) - Nielsen, Tejs Gørgens; Nielsen, Sofie Holdflod; Gravlund, Peter; Moyer, David; Galatius, Anders; Allentoft, Morten E
ABSTRACT: The African green snakes of the genus Philothamnus include c. 21 recognised species distributed across sub-Saharan Africa. Many of the species exhibit high morphological conservatism, exist sympatrically, and can have high population densities. This is presumably the reason why the number of species, their systematics, and taxonomy remain debated, and this may compromise the ability to conduct accurate species identifications based on morphological characters. To investigate and quantify this problem, we examined a large sympatric sample of ethanol-preserved Philothamnus specimens from Minziro Forest, Tanzania. Of the 248 specimens examined, 55 were P. heterolepidotus, 49 were P. hoplogaster, 33 were P. angolensis, and one was P. ornatus . A further 110 specimens could not be assigned to any species based on existing identification keys. Thus, this unidentified sample of Philothamnus comprises new forms or undescribed polymorphisms within recognised forms. We examined diagnostic morphological characters using a multivariate approach. Results revealed that if the presence or absence of the white spot character is ignored, many unidentified individuals fall within well-defined clusters based on other characters. These include the heart position, which we explore here as a new diagnostic character for this genus. A thorough revision using integrative taxonomy, for example combining morphological and genetic characteristics from across the spectrum of variability in this genus, could provide a better understanding of species limits, diversity, evolutionary history, and radiation of some of the most commonly encountered snakes in sub-Saharan Africa. This would also improve the taxonomic accuracy of regional herpetological biodiversity assessments.